EDUKASI PENCEGAHAN STUNTING MELALUI PENYULUHAN DAN PEMBERIAN MAKANAN TAMBAHAN DI DESA LAT DALAM KABUPATEN KEPULAUAN TANIMBAR - Saragih, Kristiova Masnita; Wahyunita, Vina Dwi (LPPM Institut Pendidikan Nusantara Global, 2024)
Stunting is a health problem in Indonesia. In Indonesia, the prevalence of stunted toddlers has decreased from 2021, namely 24.4% to 21.6% in 2022. In Indonesia, stunting is called stunting, meaning there is a disruption in physical growth and brain growth in children. Based on the results of the Status Monitoring survey, stunting in toddlers in the Tanimbar Islands Regency in 2022 was recorded at 31.5%, where in one village, namely Lat Dalam village, 29.41% of 221 babies and toddlers were stunted. where in one of the villages the aim of this service activity is to prevent the incidence of stunting in babies and toddlers in Lat Dalam Village. The approach used is providing health education about stunting as well as providing additional food to mothers who have babies and toddlers. As a result of the implementation of community service, it was found that 30 mothers with babies and toddlers in Lat Dalam village took part in health education regarding stunting and providing additional food. The conclusion of community service in Lat Dalam village is that mothers who have babies and toddlers are able to explain again about stunting and providing additional food.